811 Management of Patients with HPV-associated Oropharyngeal Cancer: A Units' Experience. (12th October 2021) - Fernando, S; Leow, J; Wildan, T
Abstract: Aim: The low positive predictive value (PPV) of initial post-therapy PET-CT in patients with Human papillomavirus (HPV-) associated oropharyngeal squamous cell carcinoma (OPSCC) presents a challenge for teams managing residual disease after initial treatment. We aimed to investigate current management, post treatment surveillance protocols and outcomes of these patients within our unit. Method: A retrospective review was performed of p16 positive OPSCC patients treated in 2018. Their primary treatment modality (radiotherapy (RT) or chemoradiotherapy (CRT), neck dissection), post-therapy PET-CT results, management decisions and final clinical outcomes were recorded. Results: 38 patients with p16 positive OPSCC were included in the study. 36 (94.7%) received primary CRT or RT, and 2 (5.3%) had primary neck dissections with adjuvant RT. 21 patients were found to have residual disease on the 3-month post-treatment PET-CT. Of these, 9 underwent further PET-CT surveillance, all showing no residual disease. 8 patients received ultrasound +/- fine needle aspiration, from which 1 showed incurable residual and distant metastasis. 2 underwent clinical surveillance, showing no residual disease. 1 had immediate salvage surgery, with further recurrence. 1 patient with persistent disease and lung metastasis received palliative immunotherapy. Conclusions: 31 patients were disease free at the end point of this study. This study explores the need for further investigation into features of residual disease in post treatment PET-CT that would indicate initial treatment failure and possible further early intervention. A surveillance strategy following initial post treatment PET-CT needs to be developed to aid in making this decision as early as possible in the post treatment phase.